The business of belonging: Indian migration, settlement and trade in Botswana, 1880-2012 - Spiropoulos, Lukas Nikolaos Paul (My University, 2015)
This dissertation investigates the methods used by Indian settlers to create and then retain their place in colonial Bechuanaland and post-colonial Botswana. This process, I argue, was one in which Indian migrants found ways to enter, settle and prosper in new territories, in a complex conversation with colonial powers, local politics and local and regional ecologies and geographies. They responded to the expansion of colonial commercial interests, exclusionary legislation, and settler racism through both subversive and legitimate challenges. With these they managed to forge a defensible space within the colonial system that fell between the received categories of “native” and “colonial” to form a new category which they identify as “Batswana-Indian”. The dissertation starts with a discussion of the process by which Indians settlers, mostly Gujarati, first came to the territory and their need to adapt to local economic and ecological conditions, as well as the reactions of colonial authorities to Indian immigration. The dynamics established in the early twentieth century set the terms of debate as successive administrations, from Protectorate to Republic, came to view the ‘problem’ of Indian immigration in similar ways. The thesis then delves into how these adaptive strategies actually worked. Chapter two focusses on the legal and economic marginalisation of these settlers and the consequent development of mutually beneficial relationships with certain strategically located chieftaincies, as well as the social, political and economic results of those relationships. Chapter three shows how Indian settlers – many isolated from post-partition India and driven from Apartheid South Africa - further embedded their position within Bechuanaland’s society and economy in the last two decades before independence (1966). This created an uncertain policy toward Indians that alternated between exclusion and co-option as Bechuanaland neared Independence, when the need for foreign investment grew more urgent. As the final chapter shows, Independence attracted a new wave of immigration from India, especially once its mineral riches grew lucrative. But there remained policy continuities with the colonial period, as anti-Indian rhetoric had to be balanced against Botswana’s need for investment and skills that Indian immigrants offered to fill. Culminating with an in-depth case study of the Choppies enterprise, the dissertation shows how globally connected, entrepreneurial communities from India have flourished by adapting to the ambiguities of Botswana’s policies.
A dissertation submitted to the Wits School of Social Sciences, Faculty of Humanities, University of the Witwatersrand in fulfilment of the requirements for the degree of Master of Arts. Johannesburg, 2014